Effect of land use on total phosphorus loss in selected locations - Jiří Ciml; Jiří Pečenka; Jana Moravcová; Petr Lechner; Jan Kalíšek (Acta Scientiarum Polonorum. Formatio Circumiectus)
The study focuses on how land use in the selected location affects the amount of phosphorus in the watershed. Defines the basic concepts of this and related issues. The monitored value is total phosphorus and description of the measuring apparatus. The resulting data are arranged in tables and graphs and results are compared with standards of Czech norms (CSN) and other similar studies.